2010
DOI: 10.1021/jp1006022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Denaturation of Beta-Lactoglobulin and Stabilization Mechanism by Trehalose Analyzed from Raman Spectroscopy Investigations

Abstract: The thermal denaturation process of beta-lactoglobulin has been analyzed in the 20-100 degrees C temperature range by Raman spectroscopy experiments simultaneously performed in the region of amide modes (800-1800 cm(-1)) and in the low-frequency range (10-350 cm(-1)). The analysis of amide modes reveals a two-step thermal denaturation process in the investigated temperature range. The first step corresponds to the dissociation of dimers associated with an increase of flexibility of the tertiary structure. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 50 publications
4
52
0
Order By: Relevance
“…In particular, amide I band appears very sensitive to secondary structure unfolding, whereas the low-frequency range hints for the protein-water dynamics coupling. In these studies, trehalose was found the best stabilizer of the protein secondary structure [132,181,[189][190][191][192]. By comparing protein-trehalose solutions of different composition [181,189,191], it has been observed that the main effect of trehalose is a perturbation of the tetrahedral organization of water molecules and the stiffening of the intermolecular O-H interactions necessary to stabilize the tertiary structure [190].…”
Section: Protein Stability and Denaturationmentioning
confidence: 99%
“…In particular, amide I band appears very sensitive to secondary structure unfolding, whereas the low-frequency range hints for the protein-water dynamics coupling. In these studies, trehalose was found the best stabilizer of the protein secondary structure [132,181,[189][190][191][192]. By comparing protein-trehalose solutions of different composition [181,189,191], it has been observed that the main effect of trehalose is a perturbation of the tetrahedral organization of water molecules and the stiffening of the intermolecular O-H interactions necessary to stabilize the tertiary structure [190].…”
Section: Protein Stability and Denaturationmentioning
confidence: 99%
“…Raman scattering experiments were performed also on protein-sugar solutions [14][15][16][17][18][19]. By comparing trehalose, sucrose and maltose systems, it was found out how trehalose is the most effective in stabilizing the folded secondary structure of the protein [14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, amide I band is very sensitive to the unfolding of the secondary structure, whereas the low-frequency range provides significant information on protein dynamics and on coupling of protein and hydration-water dynamics. By comparing protein-trehalose solutions at different composition [14,15,18,19], it has been confirmed that the main effect of trehalose is related to its capabilities to perturb the tetrahedral organization of water molecules and to strengthen the intermolecular O-H interactions responsible for the stability of tertiary structure [17]. In this way, the thermal stability of the HB network of water contributes to the stabilization of the native tertiary structure and inhibits the first stage of denaturation, that is, the transformation of the tertiary structure into a highly flexible state with intact secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the unfolding of β-Lg monomers in the whole temperature range studied is a single-phase reaction. The two stage denaturation model for β-Lg was previously reported by Seo et al (2010). By using Raman spectroscopy experiments, these authors suggested a first denaturation step corresponding to the dissociation of dimers, coupled with the increase of flexibility of the tertiary structure.…”
Section: Phase Diagrammentioning
confidence: 75%